Model Game Pengenalan Budaya Riau Berbasis Android Sebagai Media Pembelajaran Bagi Anak Usia Dini - Deny Dewana Hastanto; Nazruddin Safaat H; Muhammad Irsyad; Pizaini Pizaini (STMIK Banjarbaru, 2022)
The introduction of Riau culture for an early age is still in the form of visualization in the form of books and stories, because Riau culture has many customs that can be introduced, it is a pity if it is not introduced to early childhood, therefore it is hoped that related parties will cooperate in formulate strategies so that Riau culture can be introduced to early childhood. This is important because children must be nurtured to love and know their local culture from an early age. Riau culture referred to in this game include: Salaso Jatuh Kembar House, Cekak Musang Clotes, Jenawi Sword, Zapin Dance, Gambus and Patin Fish Curry. The material comes from Giyarto's book Selayang Pandang Riau. This game is built using the Multimedia Development Life Cycle (MDLC) method and uses the unity software which can later be run on an android smartphone, testing using Blackbox and User Acceptance Testing (UAT) to test the effectiveness of the game. From the results of the UAT test, it was obtained a value of 94% stating that the